Archeology in Medicine: Digging up into the tophi of Popes, Dukes and Kings - G. Ceccarelli (PAGEPress Publications, 2003)
According to an Anglo-Saxon pun, "gout is the king of diseases and the disease of Kings". In fact, it is well-known that in past times a quantity of famous persons, including Kings and Popes, were affected with this rheumatic disorder. In this paper biographical anecdotes on several Popes (Pius III, Julius II, Julius III, Clement VIII, Innocent XI, Clement XII and Pius VIII), King George IV and Queen Anne of England, as well as on some members of the Lorraine lineage, all suffering from gout, are sketched out. These historical data are briefly discussed in relation to the celebrated Hippocrates's aphorisms on gout.